Effect of preservative and preservation methods on physical, chemical and microbiological properties of nipa palm (Nypa fructicans) sap - Dayang Nur, Athirah; Mohd Razip, Asaruddin; Showkat, Ahmad Bhawani; Aldrin Felix, Simbas; Jack, Kho Swen (BioMed Central Ltd, 2025)
Objectives This study aimed to evaluate the effectiveness of the E’ food grade preservative – potassium sorbate (E202) and sodium metabisulfite (E223) in an aqueous form, and impact of the timing of preservative addition on the shelf-life, sugar and reducing sugars levels, organic acids content and microbial growth of nipa palm sap. Results The pH, sugar and reducing sugars levels, organic acids content, total bacterial count (TBC) and sensory characteristics of the sample were determined. The results showed that the treated samples were able to slow down the pH and sucrose content from dropping during storage. Sample A had lactic acid at 0.93±0.01 g/L and acetic acid at 0.05±0.0.1 g/L, while Sample B had 0.97±0.02 g/L and 0.07±0.01 g/L, respectively, both lower than the control (1.10±0.01 g/L and 0.09±0.02 g/L). Sample A with TBC of 1.03 (±0.08) x 105 CFU/mL was able to inhibit microbial growth better than Sample B, 1.14 (±0.13) x 105 CFU/mL. Preservative application prior to tapping was shown to be more successful in preserving the quality and shelf-life of nipa palm sap. This approach is likely preventing early microbial activity and fermentation without the need of proper packaging, preserving the freshness and quality of the sap more effectively than adding the preservative after collection.